Effects of Chilled Storage, Freezing Rates, and Frozen Storage Temperature on Lipid Oxidation in Meat Blocks from Cultured Bluefin Tuna Thunnus thynnus. Issue 7 (2nd October 2016) - Tanaka, Ryusuke; Nakazawa, Naho; Maeda, Toshimichi; Fukushima, Hideto; Wada, Ritsuko; Sugiura, Yoshimasa; Matsushita, Teruo; Hatate, Hideo; Fukuda, Yutaka
ABSTRACT: The effects of a short chilled storage period before freezing, frozen storage temperature, and freezing rate on lipid oxidation of bluefin tuna ( Thunnus thynnus ) meat during frozen storage were investigated. After 12-months storage, all samples had increased in peroxide value though they were less at the lower temperatures (−45 and −60°C). Peroxide values in all samples stored at −20°C increased after 3 months storage, particularly those processed and stored 51 h after harvest. The lowest increase in peroxide value occurred in the samples frozen rapidly 3 h after harvest. Vitamin E levels decreased faster during frozen storage at −20°C. There were no apparent differences in levels of triacylglycerides nor in n-3 fatty acid levels between treatments, storage periods, and storage temperatures. After 12-months storage, headspace oxidative volatiles were highest in samples stored at −20°C and lowest in those stored at −60°C. Lipid oxidation in tuna meat stored at −45°C is similar to that at −60°C, and rapid freezing rather than slow freezing should be used.